2012
DOI: 10.1371/journal.pone.0040230
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genetic Notification on Smoking Cessation: Systematic Review and Pooled-Analysis

Abstract: ObjectivesThis study aimed to evaluate the impact of genetic notification of smoking-related disease risk on smoking cessation in the general population. Secondary objectives were to assess the impact of genetic notification on intention-to-quit smoking and on emotional outcomes as well as the understanding and the recall of this notification.MethodsA systematic review of articles from inception to August 2011 without language restriction was realized using PubMed, Embase, Scopus, Web of Science, PsycINFO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…The present review indicated that improvements to smoking habits were promising in the short-term. This finding was consistent with that of a previously published systematic review of the impact of genetic notification on smoking cessation [66]. …”
Section: Discussionsupporting
confidence: 93%
“…The present review indicated that improvements to smoking habits were promising in the short-term. This finding was consistent with that of a previously published systematic review of the impact of genetic notification on smoking cessation [66]. …”
Section: Discussionsupporting
confidence: 93%
“…21 Though the baseline sample of current smokers in this study was small, these promising results suggest that genomic health information can motivate quitting. However, meta-analyses have shown that although genetic results may increase cessation motivation 11 and behaviors within 6 months, 22,23 these results are not associated with abstinence at longer follow-ups. A next step is to examine how to propagate these positive behavioral changes over the long term.…”
Section: Discussionmentioning
confidence: 99%
“…lung cancer) [5,6], and identification of genetic variants directly related to nicotine dependence [7]. This article will focus on the latter category: genetic information related to nicotine dependence.…”
Section: Introductionmentioning
confidence: 99%